a+3(2a-3b+c)+7c=

Simple and best practice solution for a+3(2a-3b+c)+7c= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for a+3(2a-3b+c)+7c= equation:


Simplifying
a + 3(2a + -3b + c) + 7c = 0
a + (2a * 3 + -3b * 3 + c * 3) + 7c = 0
a + (6a + -9b + 3c) + 7c = 0

Combine like terms: a + 6a = 7a
7a + -9b + 3c + 7c = 0

Combine like terms: 3c + 7c = 10c
7a + -9b + 10c = 0

Solving
7a + -9b + 10c = 0

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '9b' to each side of the equation.
7a + -9b + 9b + 10c = 0 + 9b

Combine like terms: -9b + 9b = 0
7a + 0 + 10c = 0 + 9b
7a + 10c = 0 + 9b
Remove the zero:
7a + 10c = 9b

Add '-10c' to each side of the equation.
7a + 10c + -10c = 9b + -10c

Combine like terms: 10c + -10c = 0
7a + 0 = 9b + -10c
7a = 9b + -10c

Divide each side by '7'.
a = 1.285714286b + -1.428571429c

Simplifying
a = 1.285714286b + -1.428571429c

See similar equations:

| P=3m+21 | | 3(5x-4y)-2(x-4y)= | | cos(2x)-sen(2x)=senx | | 2[x+4]=20 | | x^3+4x^2-4x=0 | | 6x-5=64x^2-112x+49 | | 6x-5=64x-112x+49 | | 5x(a-6b+5c)-2x(b-c)= | | 64x^2+105x+56=0 | | 1/2-x*1/2=1/8 | | 12-x=1/8 | | 14.2=7x-3.3 | | 1/2-x*51/2=1/8 | | 3xw*4w= | | 7c*4e= | | 1.5=(x-90)/15/3 | | 0=-125+20x+0.44x^2 | | 1.5=(x-90)/15/√(9) | | 8=15t-4.9t^2 | | 7x^2+9x+363=0 | | 6x-2(4y+x)= | | 3.2=28.8-8u | | 2x+4y+.125z=75 | | 10.1=5v-2.4 | | 200/86 | | 481.9/0.61 | | 2x-4x=100 | | 15x-4=3x | | 29.7-8y=4.1 | | f(3k+2)=54k^3+18k^2+12k | | 4x^3+6x^2-24x+1=0.5 | | 14x+11=-1+16x |

Equations solver categories